K modifikované koncepci "Akademického slovníku současné češtiny" - Šemelík, Martin; Lišková, Michaela; Křivan , Jan (Bohemistyka, 2023)
The presented paper is an outline of changes in the conception of the Academic Dictionary of Contemporary Czech (ADCC) for the period from 2020 onwards. We summarize the basic points of both the already implemented and planned changes in the concept and briefly characterize the future direction of work on the ADCC. The main motivation for the changes taken is the aim to finalize the dictionary core as soon as possible. In the paper we focus especially on issues regarding web design and macrostructural, microstructural as well as mediostructural phenomena. We are based, among other things, on the following postulates: (a) In accordance with the lexicographic trends of the present, the user aspect is given more emphasis in the ADCC than in the past. (b) We strive to create a lexical platform that will include various other dictionaries and offer links to corpora. (c) The ADCC is built as a growing dictionary, in the first phase the entries of 50 thousand most frequent words of contemporary Czech will be published.